Abelian Group on the Binomial Coefficients in Combinatorial Geometric Series - Chinnaraji Annamalai; Antonio Marcos de Oliveira Siqueira (The Journal of Engineering and Exact Sciences)
This paper discusses an abelian group, also called a commutative group, under addition of the binomial coefficients of combinatorial geometric series. The combinatorial geometric series is derived from the multiple summations of geometric series The coefficient for each term in combinatorial geometric series refers to a binomial coefficient. This idea can enable the scientific researchers to solve the real life problems.